PARENTING EDUCATION AND COMMUNICATION OF GENDER EQUALITY PERSUASION IN THE FAMILY ON @LATIHATI - Nurul Ifadhah; Irwansyah Irwansyah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
Internet technology innovations significantly influence various aspects of people's lives, including families. The presence of internet communication technology through New Media can educate and even persuasion the community through parenting content. Through this research, researchers describe the phenomenon of parenting education on social media, especially the Instagram platform through @latihati accounts that not only present psychological messages for the growth and development of children but also describe the importance of the presence of the role of adult men and women - in the family frame called Father and Mother. In presenting the message on @latihati, the author saw a spirit of gender equality carried out to maximize the learning pattern. An issue that is still rife in families in Indonesia where the role of mothers looks more dominant, according to un data in 2020. Through a qualitative research approach with discourse analysis, the author presents parenting education on Instagram @latihati. This was conducted through the technique of collecting interview data of @latihati account owner and observation of @latihati content whose message content is based on images and text. The purpose of this research is to prove that persuasive communication involving elements of affection- cognition consistency can lead to attitude change in equal parenting between mother’s and father’s roles as a family.